2020
DOI: 10.1175/wcas-d-18-0100.1
|View full text |Cite
|
Sign up to set email alerts
|

Initial Evidence for Increased Weather Salience in Autism Spectrum Conditions

Abstract: Weather is important to all people, including vulnerable populations (those whose circumstances include cognitive processing, hearing, or vision differences; physical disability; homelessness; and other scenarios and factors). Autism spectrum conditions affect information processing and areas of neurological functioning that potentially inhibit the reception of hazardous weather information and are of particular concern for weather messengers. People on the autism spectrum tend to score highly in tests of syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 92 publications
0
11
0
Order By: Relevance
“…Importantly, people who have had a significant interaction with the weather-a severe storm that resulted in damages or memorable event like a holiday snow storm, for examplereported overall greater weather salience. Weather salience is associated with placing greater value on weather information and forecasts (Stewart et al, 2012) and may be related to cognitive attention processes that lend themselves to its increase or decrease (Bolton, Blumberg et al, 2020;. Snow, because of its ability to dramatically alter the landscape and thus potentially disrupt the rhythm of everyday life, possesses a unique potential for engaging the mind and body (Hall & Endfield, 2016;Mergen, 1997).…”
Section: Emotional Significance Of Sensing the Weathermentioning
confidence: 99%
“…Importantly, people who have had a significant interaction with the weather-a severe storm that resulted in damages or memorable event like a holiday snow storm, for examplereported overall greater weather salience. Weather salience is associated with placing greater value on weather information and forecasts (Stewart et al, 2012) and may be related to cognitive attention processes that lend themselves to its increase or decrease (Bolton, Blumberg et al, 2020;. Snow, because of its ability to dramatically alter the landscape and thus potentially disrupt the rhythm of everyday life, possesses a unique potential for engaging the mind and body (Hall & Endfield, 2016;Mergen, 1997).…”
Section: Emotional Significance Of Sensing the Weathermentioning
confidence: 99%
“…Weather salience is driven by cognitive appraisal of, and physical sensitivity to, the natural environment (Evans & Cohen, 1987;Evans & Stecker, 2004;Stewart, 2009;Stokols, 1979Stokols, , 1995. Such attunement may predict weather knowledge and information use (Stewart et al, 2012;Williams et al, 2017) and may be enhanced in particular clinical populations and individuals with particular cognitive styles (those with autism spectrum conditions; Bolton, Blumberg et al, 2020). Recent work suggests adult weather salience may stem in part from childhood weather-learning experiences .…”
Section: Individual Difference Questionnairementioning
confidence: 99%
“…We are interested in the detail-orientation aspects of systemizing and the manner in which it drives predictions of certainty. Ideal systemizing involves keeping variables constant and changing only one parameter at a time (Baron-Cohen, 2006;Bolton, Blumberg et al, 2020) so that each change can be observed relative to the overall system. This allows for the verification of predictability through an understanding of system sensitivity (Bolton, Blumberg et al, 2020;Tullett et al, 2015).…”
Section: Individual Difference Questionnairementioning
confidence: 99%
See 2 more Smart Citations